If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying ln(x(x + -10)) = 5 Reorder the terms: ln(x(-10 + x)) = 5 ln((-10 * x + x * x)) = 5 ln((-10x + x2)) = 5 (-10x * ln + x2 * ln) = 5 (-10lnx + lnx2) = 5 Solving -10lnx + lnx2 = 5 Solving for variable 'l'. Move all terms containing l to the left, all other terms to the right. Reorder the terms: -5 + -10lnx + lnx2 = 5 + -5 Combine like terms: 5 + -5 = 0 -5 + -10lnx + lnx2 = 0 The solution to this equation could not be determined.
| 541x=803 | | -4d-6=-6d-4 | | 541x-803=64 | | 10-2q=8 | | 3+34+674= | | 30(50x+20)+40=200 | | 8*o=98 | | 5x-4+7x-18=8x+2 | | r/6+r/6=5 | | 2(2x-3)=5x-11 | | -5x^2+250x-130000=5000 | | (x^2)-19x+9.5=0 | | (x+18)=688 | | 0.4(x+7)-0.1(3x+6)=-0.8 | | 17+20-3=17y | | y=6xt+5xt^2+6 | | 15d+3.2=92 | | 3(5-3)=2(3-1) | | 2+3/5x=9 | | 4(8-2x)=-6x+4(x-4) | | 10=5-12z | | 27*n= | | 0.5x+0.2(9-x)=3.6 | | X+(x+10)+(x+15)=180 | | 3w+2(5w-3)-92=p | | 5+2/3x=9 | | -24z+10=-5 | | 4y=3x-23 | | 5y=-7x-3 | | 6+0.4x=30 | | 0=8x^2-10x-105 | | 25(x+15)+25=65 |